(untitled) (Comparative & International Education Series, 2021)
Drawing upon data from Open Doors®, this chapter highlights the characteristics of international educational exchange at HBCUs as of the most recent academic years. It provides insights into both inbound international students attending HBCUs as well as outbound U.S. students studying abroad for academic credit from HBCUs. The chapter provides statistical insights on the profile of international exchange at HBCUs compared to national trends, such as international students’ academic levels, place of origin, field of study, and primary funding source as well as U.S. study abroad students’ destination, duration of study abroad, and student characteristics.